An Evaluation of Redeploy Illinois on Juvenile Reoffending. (August 2021) - Kethineni, Sesha; Grubb, Jonathan A.
The Redeploy Illinois (RI) program was created to provide services to nonviolent, moderate to high-risk youth who were likely to be committed to the Illinois Department of Juvenile Justice (IDJJ), which oversees juvenile correctional institutions. Participating counties received financial support from the state to offer various community-based services to youth instead of incarceration. The current research evaluated the impact of the RI program in reducing recidivism from the four pilot sites during state fiscal years (FY) 2006 through 2010. Results showed that youth who completed the program had fewer convictions compared with pre-program (Pre-RI) youth as well as those who were deemed unsuccessful. The findings also demonstrated a longer survival time for RI successful youth relative to those who were unsuccessful and pre-program youth. A discussion of limitations, implications, and future directions was also provided.